Abordagem fitoquímica e avaliação da atividade antioxidante e antiinflamatória do extrato e frações da entrecasca da Mimosa hostilis Benth - Nascimento, Marcel da Silva (2013)
The use of medicinal plants for healing and prevention diseases is one of the oldest practices of mankind. Among the many plants used in folk medicine, the Mimosa hostilis Benth known as jurema black popularly used in skin problems and inflammation in general. This study aimed to perform phytochemical screening and evaluate the antioxidant and antiinflammatory activity of hydroethanolic extract (HEE) and its fractions, hexane (HXF), chloroform (CLF), ethyl acetate (EAF) and hydromethanol (HMF) obtained from the inner bark of M.hostilis. For this, the HEE and their fractions were subjected to classic phytochemical trials which involved qualitative chemical reactions that resulted in the confirmation of metabolites belonging to the classes of flavonoids, tannins, xanthones, triterpenoids, free steroids, saponins and phenols. The total phenolic content was also performed using the Folin-Ciocalteu method which it was higher in EAF (527.71 ¡Ó 30.80 mg GAE.g-1). To evaluate the antioxidant activity were used kidnapping free radical DPPH (2,2-diphenyl-1-picryl-hydrazyl) and inhibition of lipid peroxidation quantified by the thiobarbituric acid reactive substances (TBARS). The HEE, EAF and HMF had a higher inhibition percentage of DPPH free radical with indices 95.84%, 94.66% and 95.40%, respectively. The HEE and EAF showed higher lipid peroxidation inhibition percentage when induced by AAPH, while HMF was higher when induce by FeSO4. The biological activity investigated was antiinflammatory by reducing of ear edema and myeloperoxidase (MPO) activity. Ear edema was induced by 12-O-tetradecanoylphorbol acetate (TPA, 1 Ýg/ear) and the HEE effect or their fractions was evaluated by co-administration there of in doses of 1.0 and 3.0 mg/ear, with TPA in the right ear. Left ear was administered only the vehicle (acetone). After 6 h, the ear sites were removed and the edema was expressed from the mass variation between left and right ear, as well the myeloperoxidase activity (MPO) was measured. Co-administration of HEE caused significant inhibition (p<0.001) swelling and MPO activity (p<0.05) at both doses. In turn, HXF, CLF, EAF and FHM reduced similarly edema at a dose of 3.0 mg/ear and percent inhibition de 78%, 71%, 75% and 65%, respectively. The FAE and FHM inhibited MPO activity at doses 1.0 and 3.0 mg/ear (FAE: 86% and 93% for 1.0 and 3.0 mg/ear [p<0.001], respectively; FHM: 40% and 52% for 1.0 and 3.0 mg/ear [p<0.05], respectively). The CLF caused inhibition at a dose of only 3.0 mg/ear (72%, p<0.05) and HXF did not significantly alter MPO activity induced by TPA. If taken together these results indicate that the HEE and its fractions have antioxidant and antiinflammatory, allowing future studies with this plant to obtain bioactive compounds.